Iron deficiency, depression, and fatigue in inflammatory bowel diseases - König, Peter; Jimenez, Kristine; Saletu-Zyhlarz, Gerda; Mittlböck, Martina; Gasche, Christoph (Zeitschrift für Gastroenterologie, 2020)
Background Iron deficiency and anemia are common findings in IBD. Treatment of anemia improves quality of life. Neurological symptoms like depression or anxiety are also common in IBD; however, their relationship with ID has not been studied in detail.Methods Prospective, single center, non-interventional trial in an IBD cohort (n = 98), which is generally at risk for ID. Quality of sleep (using the Pittsburgh Sleep Quality Index, Epworth Sleepiness Scale, and Insomnia Severity Index) and the presence of fatigue (Piper fatigue scale), depression (Self-rating Depression Scale [SDS]) or anxiety (Self-rating Anxiety Scale [SAS]) were related to ID (ferritin, transferrin saturation), anemia (hemoglobin), and inflammatory disease activity (CRP).Results ID was present in 35 %, anemia in 16 %, and inflammation in 30 %. The overall quality of sleep in this cohort was similar to that reported for the general population. ID, anemia, or inflammation had no influence on the PSQI (median 4.0 [CI 3.0–5.0]), the ESS 5.5 (5.0–7.0), and the ISI 4.00 (2.5–5.5). Fatigue (PFS; present in 30 %), anxiety (SAS; present in 24 %), and depression (SDS; present in 33 %) were more common than in the general population. Iron deficient and anemic patients were more likely to be depressed (p = 0.02 and p < 0.01) and showed a trend towards presence of fatigue (p = 0.06 and 0.07). Systemic inflammation as measured by CRP had no effect on any of these conditions.Conclusion In this IBD cohort, ID and anemia affect depression and possibly fatigue independent of the presence of inflammation.
Keywords: IBD; iron deficiency; anxiety; depression; quality of life; quality of sleep